1978
DOI: 10.1037/0097-7403.4.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of second-order odor-aversion conditioning in neonatal rats: Implications for Kamin's blocking effect.

Abstract: It has been reported that neonatal rats acquire first-order conditioned aversions to olfactory stimulation experienced prior to drug-induced illness. Experiment 1 demonstrates that the neonate will also acquire a second-order conditioned odor aversion and that the second-order aversion is not affected by extinguishing the first-order aversion. The effectiveness of the secondorder conditioning paradigm (i.e., Si~* US; S 2 -* Sj) and a sequential blocking paradigm (i.e., S t -*US; S 2 ~*Si->US) also were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 11 publications
(31 reference statements)
7
57
1
Order By: Relevance
“…Given this information and the results of Experiments 1 and 2, it is not surprising that Experiment 3 failed to find a difference between the experimental and control groups in the extinction test for conditioning to stimulus A. This failure is, however, still surprising from the point of view of the inverse hypothesis (for other failures, see Ayres & Bombace, 1982;Cheatle & Rudy, 1978;Vom Saal & Jenkins, 1970, Experiment 1).…”
Section: Resultsmentioning
confidence: 91%
“…Given this information and the results of Experiments 1 and 2, it is not surprising that Experiment 3 failed to find a difference between the experimental and control groups in the extinction test for conditioning to stimulus A. This failure is, however, still surprising from the point of view of the inverse hypothesis (for other failures, see Ayres & Bombace, 1982;Cheatle & Rudy, 1978;Vom Saal & Jenkins, 1970, Experiment 1).…”
Section: Resultsmentioning
confidence: 91%
“…The preconditioning exposures facilitated the formation of the odor-taste association (Durlach & Rescorla, 1980;Rescorla & Cunningham, 1978) and may even have been necessary for its occurrence, since acquisition of withincompound associations has been repeatedly shown to be disrupted by the subsequent occurrence of a US (Cheatle & Rudy, 1979;Holland, 1984;Rudy, 1984). Such preexposures have also been shown to weaken enhancement of the odor aversion (Palmerino , 1979;Palmerino et al, 1980), suggesting that they tend to reduce the probability of associative potentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dickinson, Hall, and Mackintosh (1976) reported that omitting an expected US in the compound conditioning stage of the Kamin blocking procedure alleviated blocking to the target element (i.e., enhanced conditioning). Similarly, Cheatle and Rudy (1978) reported that if a neutral stimulus, X, was compounded with a preconditioned stimulus, A, X would gain second-order conditioned strength only if the US used to precondition A did not follow the AX compound. And Hall and Pearce (1982) reported that "associability" could be restored to a CS that had lost it through repeated pairings with a weak US by omitting the US on one or two trials before pairing the CS with a stronger US in the next stage.…”
Section: Methodsmentioning
confidence: 99%